By the river piedra i sat down and wept - Coelho, Paulo (Thorsons London, 2014)
"By the River Piedra I Sat Down and Wept" is a novel by Paulo Coelho that tells the story of Pilar, a woman who embarks on a transformative journey of self-discovery and love. After years of separation, Pilar reunites with her childhood love, a man who has chosen a spiritual path as a monk. As they travel together along the banks of the Piedra River, they confront their past, explore their emotions, and grapple with the complexities of faith, love, and destiny. The novel beautifully weaves themes of spirituality, longing, and the search for personal fulfillment, inviting readers to reflect on the nature of love and the courage to follow one's heart.